Bioinformatics in molecular immunology laboratories demonstrated: modeling an anti-CMV scFv antibody - Chua, K.H.; Othman, R.Y. (2006)
A scFv (single chain variable fragment) antibody clone from anti-CMV (anti-cucumber mosaic virus) was successfully constructed from immunized mouse and the DNA sequence was submitted to GenBank (AY337618 and AY337619). The expression of a 32 kDa recombinant antibody in bacteria was verified using ELISA (enzyme-linked immunoassay) and western blot. However, elucidation of specific anti-CMV scFv function requires detailed and time consuming immuno-assays. Alternatively, useful functional information on anti-CMV scFV antibody can be obtained using available Bioinformatics tools and techniques without performing tedious assays. Here, we use the commonly used Bioinformatics tools and databases such as BLAST (basic local alignment search tool), GenBank, PDB (protein databank), KABAT numbering, SWISS-MODEL and Insight II to gain specific functional insights into anti-CMV scFv.